Application of fluorescein sodium in the resection of vermis pilocytic astrocytomas. Issue 1 (December 2017) - Zhang, Ji; AL-Nahari, Fuad; Wang, Zi-feng; Lin, Fu-hua; Zhao, Yi-yin; Xiao, Shi-yin; Liu, Jian-min; Ke, Chao; Chen, Zheng-he; Jiang, Yu; Yang, Men; Sai, Ke; et al.
Abstract Background Pilocytic astrocytomas (PAs) are slow growing neoplasms and usually located at the cerebellum. There has been certainty regarding the truthful benefit of surgical resection for patients with PA. Gross total resection (GTR) of PAs, especially those being situated in deep regions, remains a surgical challenge. Generally, they are considered as benign and usually develop in young patients. PAs, belonging to WHO I can be cured by radical resection. The patients with PA have excellent prognosis if complete resection can be conducted. The use of fluorescein in vermis PA surgery has not been yet reported. Our data presents fluorescein facilitates surgical resection of vermis PA. Methods Five milligrams per kilogram of fluorescein sodium was intravenously injected directly before general anesthesia for the three patients with PA. The yellow 560 filter was employed for microsurgical tumor resection. Surgical outcomes were assessed concerning the extent of resection. Results Most portion of PA in the three cases was found to be highly fluorescent after intravenous fluorescein sodium injection, which markedly enhanced tumor visibility. Gross total resection in all of the patients was achieved without further neurological deficits. No adverse effects and complications resulting from fluorescein sodium were observed over the postoperative course. Conclusions Intraoperative guidance by fluorescein sodium as a new, simple, safe, and practical procedure can enhance the fidelity of tumor tissue and increase the possibility of completely resecting PAs.